Anisotropic Wettability on Imprinted Hierarchical Structures - Zhang, Fengxiang; Low, Hong Yee (Langmuir, 2007)
A series of two-level hierarchical structures on polystyrene (PS) and poly(methyl methacrylate) (PMMA) were fabricated using sequential nanoimprinting lithography (NIL). The hierarchical structures consist of micrometer and sub-micrometer scale grating imprinted with varying orientations. Through water contact angle measurements, these surface hierarchical structures showed a wide range of anisotropic wettabilities on PMMA and PS, with PMMA having an anisotropic wettability from 6° to 54° and PS having an anisotropic wettability from 8° to 32°. At the same time, the water contact angle of PMMA and PS can be tuned to nearly 120° without modifying the surface chemistry. A tunable anisotropic wettability is beneficial for applications where controlling the direction of liquid flow is important, such as in microfluidic devices.